212k views
0 votes
-----------------> 10x - 3 - 2x = 4

User Tue Nguyen
by
5.1k points

2 Answers

3 votes

Answer:

x=7/8

Explanation:

10x-3-2x=4

collect like term

8x-3=4

move constant to the right-hand side and change its sign

8x-3=4 into 8x=4+3

add up the number : 8x=4+3

8x=7 divide both sides of the equation by 8

x = 7/8

User Jeeten Parmar
by
4.5k points
3 votes

Answer:


x=(7)/(8)

Explanation:


10x-3-2x=4

First, collect and rearrange the like terms.


10x-3-2x=4


8x-3=4


8x=4+3

Then, solve the equation:


8x=4+3


8x=7


x=(7)/(8)

So, the answer is
x=(7)/(8). Hope my solution and explanation can help you. Thank you!

If you still cannot get the point, you can ask me anytime.

User GolezTrol
by
3.7k points